A study on The Level of Environmental Pollution by Heavy Metals in The City of Sebha-Libya - Fadhil Abbas, Kafaa; Basi, M A; Al-Shareef, I M (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Abstract: The concentration of a number of heavy metals Lead, Cadmium, Zinc, Copper, Cobalt, Nickel and Iron was studied in the recent deposits of Sebha city. It was found that the concentration were below the pollution level and the concentration falls within the range of the natural concentrations of similar sediments in the different areas of the world. The concentration rates were as follows: Pb 10.06 ppm, Cd 0.09 ppm, Zn 1.88 ppm, Cu 0.79 ppm, Co 0.64 ppm, Ni 1.03 ppm and Fe 384.55 ppm. The results also indicated that the high concentrations of Pb, Zn, and Fe at the edge of the roads and the decrease with depth might be reflected the role of the different means of transportation represented by hydrocarbon’s exhausts in the concentration of these elements.